2013
DOI: 10.1093/nar/gkt158
|View full text |Cite
|
Sign up to set email alerts
|

HP1a, Su(var)3-9, SETDB1 and POF stimulate or repress gene expression depending on genomic position, gene length and expression pattern in Drosophila melanogaster

Abstract: Heterochromatin protein 1a (HP1a) is a chromatin-associated protein important for the formation and maintenance of heterochromatin. In Drosophila, the two histone methyltransferases SETDB1 and Su(var)3-9 mediate H3K9 methylation marks that initiates the establishment and spreading of HP1a-enriched chromatin. Although HP1a is generally regarded as a factor that represses gene transcription, several reports have linked HP1a binding to active genes, and in some cases, it has been shown to stimulate transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 68 publications
7
48
0
Order By: Relevance
“…We examined profiles from Su(var) 3-9 06/evo , SetDB1 10.1 , and HP1 04/05 mutant first-instar larvae (Lundberg et al, 2013) and Pc-and Pho-RNAi knockdown embryos (Goodliffe et al, 2007). Intriguingly, $70% overlap was observed between our significantly dysregulated IGMR genes and those responsive to H3K9-centric or polycomb insufficiency ( Figures 5F and 5G).…”
Section: The Igmr Program Is Chromatin Encodedmentioning
confidence: 94%
See 2 more Smart Citations
“…We examined profiles from Su(var) 3-9 06/evo , SetDB1 10.1 , and HP1 04/05 mutant first-instar larvae (Lundberg et al, 2013) and Pc-and Pho-RNAi knockdown embryos (Goodliffe et al, 2007). Intriguingly, $70% overlap was observed between our significantly dysregulated IGMR genes and those responsive to H3K9-centric or polycomb insufficiency ( Figures 5F and 5G).…”
Section: The Igmr Program Is Chromatin Encodedmentioning
confidence: 94%
“…To test whether these signatures might directly contribute to metabolic reprogramming, we performed GSEA analysis of the Lundberg et al (2013) and Goodliffe et al (2007) data sets. Coordinate overlapping enrichment signatures were observed for key pathways of all five major IGMR clusters ( Figure 5M and Table S2), including most chromatin and primary energy modules.…”
Section: The Igmr Program Is Chromatin Encodedmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the endo-siRNA pathway is predominantly active in nongonadal somatic cells, we speculate that the absence of H3K9 disrupts this pathway. Previous studies have demonstrated that mutations in H3K9 methyltransferases and HP1 result in transposon activation (Brower-Toland et al 2009;Lundberg et al 2013). Increased piRNA levels could therefore be a response to this activation.…”
Section: H3k9 Regulation Of Gene Expression and Transposonsmentioning
confidence: 99%
“…The presence and degree of spreading differed between nuclei, and we typically saw 1-3 bands decorated by POF in both PoX1 and PoX2 . In addition to the two loci on the X-chromosome, we occasionally observed POF binding in parts of the 2L:31 region in both males and females (Figure 1) (Lundberg et al 2013). …”
Section: Resultsmentioning
confidence: 90%